Pelatihan Tote Bag Teknik Eco-Shibori Kolaborasi Nusa Creative Community - Nofisulastri, Nofisulastri; Adawiyah, Siti Rabiatul; Dharmawibawa, Iwan Doddy; Sarifuddin, Muhamad (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
Training on making cloth tote bags is one of the government's programs to reduce the use of plastic, is the right step, and as a citizen you should also support this program. Support in training to make cloth shopping bags (Tote Bags) that can be used to carry groceries when shopping at super markets, supermarkets, or department stores, so that consumers are expected to no longer use plastic bags when shopping. The choice of a fabric tote bag with the Eco-Shibori technique in this service activity is an illustration of eco-friendly ecoprint or eco-dyeing techniques, which are in great demand and are recognized as having high selling value. The target of the activity was 14 people, including representatives of 6 female students from Private MA Annajah Sesela, Gunungsari District, West Lombok Regency, 5 MTs students. Private Annajah Sesela, Gunungsari District, West Lombok Regency, and 3 students from Mataram Janamarga High School, Mataram City. The activities will be carried out from 3 October - 4 December 2022, with the overall activity stages, namely communication, observation, legalization, training on making the Eco-Shibori Tote Bag technique, and evaluation of activity responses. Based on the evaluation, activity responses obtained 98-100% understanding of shibori batik and being able to take part in training demonstrations, and being able to work collaboratively to create eco-prints on Tote Bags from various leaves provided and or obtained from the surrounding environment.